Additional chemoradiotherapy following endoscopic submucosal dissection in patients with esophageal squamous cell carcinoma: a narrative review - Lin, Yan; Wang, Shou-Feng; Liang, Huan-Wei; Liu, Yang; Huang, Wei; Pan, Xin-Bin (Frontiers in Oncology, 2025)
This review offers a critical synthesis of additional therapeutic strategies following endoscopic submucosal dissection (ESD) for esophageal squamous cell carcinoma, providing evidence-based recommendations to optimize clinical decision-making. For pT1a-EP/LPM lesions, ESD alone demonstrates curative potential with lymph node metastasis rates ranging from 0.0% to 3.3%. In contrast, pT1b-MM tumors exhibiting lymphovascular invasion warrant adjuvant chemoradiation therapy, associated with 21.4% nodal metastasis rates. For pT1b-SM1 lesions, chemoradiation is indicated-particularly demonstrating 13.2% nodal involvement without lymphovascular invasion versus 60.0% metastasis risk in cases with vascular invasion during observation. Timing of additional chemoradiotherapy should be expedited, with immediate initiation (1–2 months post-ESD) showing superior outcomes. Radiation dosing optimization reveals equivalent efficacy between ​​lower radiation doses (40-41.4 Gy) and higher doses (50-50.4 Gy), with reduced treatment-related toxicity. Target volume delineation should prioritize the ESD bed with appropriate margins over elective nodal coverage, maintaining therapeutic efficacy while minimizing radiation exposure. The role of concurrent chemotherapy remains controversial, with retrospective evidence suggesting definitive radiotherapy may provide comparable local control.